Automated cold temperature cycling improves in vitro platelet properties and in vivo recovery in a mouse model compared to continuous cold storage. Issue 1 (1st September 2015) - Skripchenko, Andrey; Gelderman, Monique P.; Awatefe, Helen; Turgeon, Annette; Thompson‐Montgomery, Dedeene; Cheng, Chunrong; Vostal, Jaroslav G.; Wagner, Stephen J.
Abstract : BACKGROUND: Platelets (PLTs) stored at cold temperatures (CTs) for prolonged time have dramatically reduced bacterial growth but poor survival when infused. A previous study demonstrated that human PLTs stored with manual cycling between 4°C (12 hr) and 37°C (30 min) and infused into severe combined immunodeficient (SCID) mice had survivals similar to or greater than those stored at room temperature (RT). In this study, the in vitro and in vivo properties of PLTs stored in an automated incubator programmed to cycle between 5°C (11 hr) and 37°C (1 hr) were evaluated. STUDY DESIGN AND METHODS: A Trima apheresis unit ( n  = 12) was aliquoted (60 mL) in CLX bags. One sample was stored with continuous agitation (RT), a second sample was stored at 4‐6°C without agitation (CT), and a third sample was placed in an automated temperature cycler with 5 minutes of agitation during the warm‐up period (thermocycling [TC]). PLTs were assayed for several relevant quality variables. On Day 7, PLTs were infused into SCID mice and in vivo recovery was assessed at predetermined time points after transfusion. RESULTS: The glucose consumption rate, morphology score, hypotonic shock recovery level, and aggregation levels were increased and mitochondrial reactive oxygen species accumulations were decreased in TC‐PLTs compared to those of CT‐PLTs. The pH and Annexin V binding were comparable to those of RT‐PLTs. All TC‐PLTs had greater recovery than CT‐PLTs and were comparable to RT‐PLTs. CONCLUSION: PLTs stored under automated TC conditions have improved in vivo recovery and improved results for a number of in vitro measures compared to CT‐PLTs.